Stock Price Determinant Through Capital Structure As Intervening Variables In Construction Companies Listed In Indonesian Stock Exchange - Aryani, Florida; Yustisiana, Riska; Andhyka, Bintang; Widyaningsih, Murti (The journal of contemporary issues in business and government, 2021)
Changes in macroeconomic conditions affect various things such as changes in interest rates that have an impact on companies with debt on their capital structure. Likewise, the company's profitability and profit growth can affect the company's capital structure which then affects the stock price, especially in construction companies.This study aims to describe and analyze the influence of interest rate, profit growth and profitability of stock price through capital structure. The sample is construction companies listed in Indonesian Stock Exchange in the 2014-2019 period and the observation is through purposive sampling method. Analytical techniques used are multiple linear analysis and path analysis. The results show that interest rate, profit growth, and profitability affect capital structure. Interest rate and capital structure affect stock price while profit growth and profitability has no effect on stock price. Capital structure mediates the influence of interest rate, profit growth and profitability on stock price.